Global characterization of the SRC-1 transcriptome identifies ADAM22 as an ER-independent mediator of endocrine resistant breast cancer - McCartan, Damian (2011)
The development of breast cancer resistance to endocrine therapy results from an increase in cellular plasticity that permits the emergence of a hormone independent tumor. The steroid coactivator protein SRC-1, through interactions with developmental proteins and other non-steroidal transcription factors, drives this tumor adaptability. In this discovery study we identified ADAM22, a non-protease member of the ADAM family of disintegrins, as a direct ER-independent target of SRC-1. We confirmed SRC-1 as a regulator of ADAM22 by molecular, cellular and in vivo studies. ADAM22 functioned in cellular migration and differentiation and its levels were increased endocrine resistant tumors compared to endocrine sensitive tumors in a mouse xenograft models of human breast cancer. Clinically ADAM22 was found to serve as an independent predictor of poor disease-free survival. Taken together, our findings suggest that SRC-1 switches steroid-responsive tumors to a steroid resistant state in which the SRC-1 target gene ADAM22 has a critical role, suggesting this molecule as a prognostic and therapeutic drug target that could help improve the treatment of endocrine-resistant breast cancer.